EVALUATION OF ORTHODONTIC TREATMENT NEED AND ITS ASSOCIATION WITH SELF-ESTEEM AND ORAL HEALTH-RELATED QUALITY OF LIFE OF PATIENTS RECEIVING CARE AT SAIDU COLLEGE OF DENTISTRY, SWAT - KHAN, EB; QURESHI, AH; JAFRI, AR; AHMAD, M; RASHID, HU; NAZ, H; KAINAT, .; KHAN, JA (Biological and Clinical Sciences Research Journal, 2024)
Orthodontic treatment needs can impact both self-esteem and oral health-related quality of life (OHRQoL). The relationship between these factors, particularly in a developing region, remains underexplored. Objective: To investigate the relationship between orthodontic treatment needs, self-esteem and oral health-related quality of life among patients at Saidu College of Dentistry, Swat. Methods: This cross-sectional study was conducted at Saidu College of Dentistry, Swat and included 115 participants aged 8-30 years. Data were collected using the Index of Orthodontic Treatment Needs (IOTN), Rosenberg Self-esteem Scale and Oral Health Impact Profile (OHIP-14) over a six-month period. Demographic variables such as age, gender and socioeconomic status were also analyzed. Descriptive statistics and statistical tests such as chi-square and t-tests were employed to evaluate associations between variables, with significance set at p < 0.05. Results: Of the 115 participants, 59.1% were male and 40.9% were female. Age groups were distributed as 33% (8-15 years), 39.1% (15-22 years) and 27.8% (22-30 years). Socioeconomic analysis revealed that 25.2% belonged to the upper class, 49.6% to the middle class and 25.2% to the poor class. Severe orthodontic treatment needs were identified in 36.5% of participants. Self-esteem scores were unaffected by gender, age, or socioeconomic status. In contrast, oral health impact scores were notably high, with a mean OHIP-14 score of 19.77±17.7, indicating a significant need for comprehensive oral health care. Conclusion: Despite high orthodontic treatment needs, participants exhibited stable self-esteem levels, suggesting resilience in psychosocial health. The findings emphasize the strong connection between orthodontic needs, OHRQoL and patient demographics, providing important insights for oral health professionals in addressing both clinical and psychological aspects of care.